Pengaruh Model Pembelajaran Mind Mapping Berbantuan Media Audio Visual Terhadap Minat Belajar IPA Siswa SDN Wirogomo 01 - Maulida, Maulida; Suryani, Ela (Universitas PGRI Semarang, 2022)
The purpose of this study was to determine the effect of using mind mapping learning models assisted by audio-visual media on interest in learning science in class V SDN Wirogomo 01. This research method was a quasi-experimental design with a non-equivalent design type. Samples were taken by purposive sampling technique. SDN Wirogomo 01 as the experimental class and SDN Wirogomo 02 as the control class. This study uses a questionnaire/questionnaire data collection technique, observation, interviews and documentation. The data analysis technique used was the Normality Test, Homogeneity Test, T-Test and Simple Linear Regression Test. The results of this study indicate: 1. There are differences in the use of mind mapping learning models assisted by audio-visual media on students' interest in learning, this is evidenced by the significance level 0.05, which is 0.000 less than 0.05 and 2. There is an effect of using the mind mapping learning model. assisted by audio-visual media on students' interest in learning, this is evidenced by a significant level of 0.05, which is 0.000 less than 0.05.